THE APPLICATION OF MELTS GAS SPRAYING TECHNOLOGY FOR OBTAINING MAGNETIC MATERIALS - Ternovyy, Yuri; Lichkonenko, Natali (Scientific Journal "Metallurgy", 2022)
The possibility of applying the method of gas spraying of the melt to obtain permanent magnets based on the Fe-Nd-B system is considered. It is shown that in recent decades the volume of PM production based on intermetallic compounds of rare earth metals with iron has been growing intensively. The magnetic properties of sintered PM from Fe-Nd-B alloys depend in a complex way on their composition and structure, which, in turn, are determined by the methods of their production. The possibilities, advantages and disadvantages of different methods of production of magnetically hard materials are highlighted. It is shown that the method of gas spraying due to high melt velocities in the cooling process makes it possible to provide for many complex-alloyed alloys supercooling sufficient for the formation of a homogeneous chemical and structural-phase composition. Samples of Fe-Nd-B alloy were experimentally obtained by a technology that includes smelting the alloy in an induction furnace, spraying the obtained melt with heated inert gas, pressing the powder in an orienting magnetic field, sintering and subsequent heat treatment. The presented comparative results of measurements of magnetic properties of material based on Fe-Nd-B alloy show that the optimal gas heating temperature can be considered 523 K. Thus, the use of fine powder obtained by heating energy gas for the production of magnetoplastics allows to increase the level and stability of magnetic properties of permanent magnets of the Fe-Nd-B system.